Weight analysis of Chinese nurses' behaviors to maintain patient dignity and its relationship with job-esteem: a cross-sectional study controlling for agreeableness - Guo, Cong; Zhang, Chunlin; Zhou, Cuizhu; Zhu, Mengqi; Chen, Lingling; Liu, Youran; Zhang, Yequn; Wang, Jie; Liang, Tengfei (Frontiers in Psychology, 2026)
BackgroundPatient dignity is fundamental to nursing ethics and care quality, yet nurses often face challenges in upholding it. This study examines how nurses' Job-Esteem influences their behaviors for maintaining patient dignity in China.MethodsThis two-stage study was conducted in 2025. The first round (April) employed convenience sampling at a hospital in Anhui Province, yielding 508 valid responses. The second round (November) utilized a multi-stage random sampling across five hospitals in East and Central China, yielding 496 valid responses, resulting in a total of 1,004 valid questionnaires. All participants were assessed using the Dignity in Care Scale for Nurses, Job-Esteem Scale for Nurses in Hospital, and Chinese Big Five Personality Inventory brief version. Hierarchical regression was used for analysis.ResultsThe total score of Nurses' Behaviors to Maintain Patient Dignity was 168.00(145.00,180.00), and the total score of Job-Esteem was 112.00(99.00,124.00). Job-Esteem explained an additional 42% of the variance in Nurses‘ Behaviors to Maintain Patient Dignity. Key predictors included professional competence (β = 0.29), professional self-awareness (β = 0.18), respect and recognition of the organization (β = 0.19), and social trust and Respect (β = 0.15). Weight analysis indicated that the “Patient Care Needs Promptly (PCNP)” dimension had the highest weight (17.50%).ConclusionJob-Esteem was significantly associated with Nurses' Behaviors to Maintain Patient Dignity. Our findings suggest that interventions focused on enhancing professional competence, strengthening organizational support, and addressing Patient Care Needs Promptly may be promising avenues for advancing dignity-based care.